2019
DOI: 10.1111/are.13986
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide comparative analysis of theSHSP,HSP60/10andHSP90genes reveals differential heat stress responses in estivation of the sea cucumberApostichopus japonicus

Abstract: Small HSP (SHSP), HSP60/10 and HSP90 are subgroups of heat shock proteins and play important roles in cytoprotective, housekeeping and apoptosis regulatory functions. These proteins are always involved in the response to stressful stimuli, especially heat stress. In this study, 10 SHSPs, two HSP60/10s and three HSP90s were identified and systematically characterized from the transcriptome and genome of the sea cucumber Apostichopus japonicus. According to the results of phylogenetic and syntenic analyses, alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…The results showed that AjHSP70IVAs were significantly upregulated in both body walls and muscle tissues throughout the aestivation period [ 143 ]. In a subsequent genome-wide analysis, Gao et al found that small HSP (SHSP) proteins play a key role in stress relief in mature individuals, whereas AjHSP60/10s and AjHSP90s are more likely to play a role in housekeeping [ 144 ]. Another study by Gao et al demonstrated that the co-chaperone protein of HSP70, DNAJ, promotes protein folding and degradation under environmental stress and that AjHSP70IVAs in A. japonicus are regulated by AjDNAJs during aestivation.…”
Section: Characteristics and Research Progress Of Invertebrate Aestiv...mentioning
confidence: 99%
“…The results showed that AjHSP70IVAs were significantly upregulated in both body walls and muscle tissues throughout the aestivation period [ 143 ]. In a subsequent genome-wide analysis, Gao et al found that small HSP (SHSP) proteins play a key role in stress relief in mature individuals, whereas AjHSP60/10s and AjHSP90s are more likely to play a role in housekeeping [ 144 ]. Another study by Gao et al demonstrated that the co-chaperone protein of HSP70, DNAJ, promotes protein folding and degradation under environmental stress and that AjHSP70IVAs in A. japonicus are regulated by AjDNAJs during aestivation.…”
Section: Characteristics and Research Progress Of Invertebrate Aestiv...mentioning
confidence: 99%